2014
DOI: 10.1186/1476-7120-12-34
|View full text |Cite
|
Sign up to set email alerts
|

Intima media thickness, pulse wave velocity, and flow mediated dilation

Abstract: The identification of vascular alterations at the sub-clinical, asymptomatic stages are potentially useful for screening, prevention and improvement of cardiovascular risk stratification beyond classical risk factors.Increased intima-media thickness of the common carotid artery is a well-known marker of early atherosclerosis, which significantly correlates with the development of cardiovascular diseases. More recently, other vascular parameters evaluating both structural and functional arterial proprieties of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
49
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(51 citation statements)
references
References 91 publications
0
49
0
2
Order By: Relevance
“…Endothelial dysfunction (ED) has been shown to be predictive of subsequent cardiovascular events and death. [38][39][40] Recent studies clearly showed that continuous administration of a high salt (300-350 mmol Na + /d or 6.9-8.0 g Na + /d) diet for 1 week impaired forearm endothelium-dependent vasodilation 41 and cutaneous microvascular function 42 independent of BP and serum sodium concentration. High salt intake has been shown to generate oxidative stress, reducing bioavailable NO and endothelium-dependent dilation in humans, 42 mice, 43 and rats.…”
mentioning
confidence: 99%
“…Endothelial dysfunction (ED) has been shown to be predictive of subsequent cardiovascular events and death. [38][39][40] Recent studies clearly showed that continuous administration of a high salt (300-350 mmol Na + /d or 6.9-8.0 g Na + /d) diet for 1 week impaired forearm endothelium-dependent vasodilation 41 and cutaneous microvascular function 42 independent of BP and serum sodium concentration. High salt intake has been shown to generate oxidative stress, reducing bioavailable NO and endothelium-dependent dilation in humans, 42 mice, 43 and rats.…”
mentioning
confidence: 99%
“…Pulse wave velocity (PWV) is the main index for estimating arterial elasticity. This reliable, repeatable and noninvasive method is easy to practice and useful in detecting increased stiffness at the early stage 7 . Pulse wave velocity can be measured by applanation tonometry, oscillometry or vascular ultrasound on several arterial sites 8 .…”
mentioning
confidence: 99%
“…EF was assessed by measuring the FMD of the brachial artery, a reliable and accurate non-invasive ultrasound technique [37]. Baseline FMD was below 6% in approximately 75% of the 78 subjects screened for the study, reflecting a condition of moderate ED in our population.…”
Section: Discussionmentioning
confidence: 99%